Importance of fractional exhaled nitric oxide in diagnosis of bronchiectasis accompanied with bronchial asthma - Chen, Feng-Jia; Liao, Huai; Huang, Xin-Yan; Xie, Can-Mao (Journal of Thoracic Disease, 2016)
Background: Fractional exhaled nitric oxide (FeNO) measurement is a simple, rapid, highly reproducible, and noninvasive method of airway inflammation assessment. Therefore, FeNO is extensively used for the diagnosis and management of asthma. The feasibility of using FeNO as an alternative to conventional pulmonary function test to differentiate patients with bronchiectasis (BE) and bronchial asthma from those with BE only remains unclear. Methods: From February 2013 to February 2015, 99 patients diagnosed with BE through high-resolution computed tomography (HRCT) were subjected to FeNO measurement, bronchial challenge test (BCT), or bronchodilator test. Bronchial hyperreactivity and/or reversible airway obstruction was used to define asthma. The receiver operating characteristic (ROC) curves were obtained to elucidate the clinical functions of FeNO in the diagnosis of asthmatic patients with BE, and the optimal operating point was also determined. Results: Of 99 patients with BE, 20 patients presented asthma, and 12 of these patients received regular treatment, which were given with budesonide (200 μg, bid) for 12 weeks to evaluate changes in the concentration and assess the role of FeNO in the treatment. The area under the ROC curve was estimated as 0.832 for FeNO. Results also revealed a cut off value of >22.5 part per billion (ppb) FeNO for differentiating asthmatic from non-asthmatic (sensitivity, 90.0%; specificity, 62.5%) patients with BE. FeNO and forced expiratory volume for 1 second significantly improved after the treatment. Conclusions: Clinical FeNO measurement is a simple, noninvasive, and rapid method used to differentiate asthmatic from nonasthmatic patients with BE. This technique exhibits potential for asthma management.